Sahasrayogam : Compendium of 1000 + ayurvedic formulations : Sanskrit text with English translation and Prabhakara vyākhyānam - Prabhakara Rao, G.; Prabhakara Rao, G. (Chaukambha, 2016)
Work on Ayurvedic system of Indic medicine.